2019
DOI: 10.1016/j.cct.2019.105888
|View full text |Cite
|
Sign up to set email alerts
|

A pilot multisite study of patient navigation for pregnant women with opioid use disorder

Abstract: The opioid crisis continues to affect pregnant and postpartum women the United States, with the number of pregnant women diagnosed with opioid use disorder (OUD) quadrupling over the last decade. The associated increase in morbidity and mortality among mother and baby warrants prompt, targeted intervention efforts that improve engagement, linkage of care, and treatment retention. Patient navigation (PN) is a chronic care intervention that can directly address this need by helping women identify medical, behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…The parent study of the current project was Optimizing Pregnancy and Treatment Interventions for Moms 2.0 (OPTI-Mom 2.0) (NCT03833245), a prospective clinical trial testing the efficacy of a patient navigator intervention to facilitate linkage to MOUD treatment engagement and psychosocial services among PPP-OUD ( 24 ). Details of the protocol can be viewed elsewhere ( 24 ) and are summarized here in brief to relate those most relevant to the current study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The parent study of the current project was Optimizing Pregnancy and Treatment Interventions for Moms 2.0 (OPTI-Mom 2.0) (NCT03833245), a prospective clinical trial testing the efficacy of a patient navigator intervention to facilitate linkage to MOUD treatment engagement and psychosocial services among PPP-OUD ( 24 ). Details of the protocol can be viewed elsewhere ( 24 ) and are summarized here in brief to relate those most relevant to the current study.…”
Section: Methodsmentioning
confidence: 99%
“…The parent study of the current project was Optimizing Pregnancy and Treatment Interventions for Moms 2.0 (OPTI-Mom 2.0) (NCT03833245), a prospective clinical trial testing the efficacy of a patient navigator intervention to facilitate linkage to MOUD treatment engagement and psychosocial services among PPP-OUD ( 24 ). Details of the protocol can be viewed elsewhere ( 24 ) and are summarized here in brief to relate those most relevant to the current study. OPTI-Mom 2.0 participants included pregnant individuals ≤32 weeks of gestation presenting with OUD at University of Utah Hospital and Magee-Womens Hospital of UPMC, which are tertiary, academic medical centers providing general and specialty services to urban, suburban, and rural populations in Utah and Western Pennsylvania, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Those who attended substance use treatment program support groups cited their peers as "significant source(s) of support and information, " and many people found comfort in hearing the stories of other births following treatment for OUD (Goodman et al, 2020). One-toone clinical support to assist patients in navigating the healthcare system and other sources of assistance has also been cited as a way to help people engage with medical providers, overcome barriers, and set goals for themselves and their newborns (Cochran et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study protocol and methods have been reported previously. 5 Participants were recruited from two academic tertiary care medical centers (University of Utah and the University of Pittsburgh). Both centers have perinatal addiction clinics tailored to this population.…”
Section: Methodsmentioning
confidence: 99%
“…Demographics of respondents, including race and ethnicity, were reported, because they are important social determinants of OUD treatment and overdose disparities. [5][6][7] Overdose history was ascertained using the OESWD (Overdose Experiences, Self and Witnessed-Drug Assessment) tool, a validated tool for assessing these events among individuals who use drugs. [8][9][10] Participants completed six questions about prior overdose events at study enrollment, which ranged between 7 and 32 weeks of gestation.…”
Section: Methodsmentioning
confidence: 99%